2015
DOI: 10.11646/phytotaxa.208.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Passiflora echinasteris: a new species of subgenus Passiflora, series Serratifoliae (Passifloraceae) from the Brazilian Amazon

Abstract: Passiflora echinasteris from a secondary vegetation area on the Great Curve of the Xingu River, in the Brazilian Amazon, is newly described. It belongs to the series Serratifoliae with three other Brazilian species. The new species is illustrated and its affinities with related species are discussed, and a key to the Brazilian species of the series is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In Brazil, Passiflora Linnaeus (1753, p. 955) is represented by 153 species, of which 76 occur in the Amazonia domain (BFG 2015, 2018). In the last decade, taxonomic studies of Passiflora from the Brazilian Amazon have demonstrated the expressive importance of this genus, and seven new taxa have been described: Passiflora kikiana Cervi and Linsingen (2010, p. 1062), P. cristalina Vanderplank and Zappi (2011, p. 149), P. fissurosa Souza and Hopkins (2011, p. 449), P. longifilamentosa Koch et al (2013, p. 43), P. echinasteris Koch et al (2015, p. 171), P. lorenziana Mezzonato‐Pires et al (2016, p. 78), P. bernaccii Mezzonato‐Pires (2018, p. 230) and P. garckei subsp. pentaloba Engels & A.K.Koch (2019, p. 17).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, Passiflora Linnaeus (1753, p. 955) is represented by 153 species, of which 76 occur in the Amazonia domain (BFG 2015, 2018). In the last decade, taxonomic studies of Passiflora from the Brazilian Amazon have demonstrated the expressive importance of this genus, and seven new taxa have been described: Passiflora kikiana Cervi and Linsingen (2010, p. 1062), P. cristalina Vanderplank and Zappi (2011, p. 149), P. fissurosa Souza and Hopkins (2011, p. 449), P. longifilamentosa Koch et al (2013, p. 43), P. echinasteris Koch et al (2015, p. 171), P. lorenziana Mezzonato‐Pires et al (2016, p. 78), P. bernaccii Mezzonato‐Pires (2018, p. 230) and P. garckei subsp. pentaloba Engels & A.K.Koch (2019, p. 17).…”
Section: Introductionmentioning
confidence: 99%
“…Taxonomic studies of Passifloroideae have already been carried out in some Brazilian states and regions of Brazil, such as Amazonia (Souza & Hopkins, 2011; Cervi & Linsingen, 2010; Koch et al, 2015; Mezzonato‐Pires et al, 2016), southeast of Pará in the Serra dos Carajas (Koch & Ilkiu‐Borger, 2016), Mato Grosso (Cervi & Imig, 2013; Mezzonato‐Pires, Silva & Oliveira, 2021; Silva et al, 2013), Mato Grosso do Sul (Koch et al, 2019), São Paulo (Groppo & Pirani, 2005), Espírito Santo (Imig & Cervi, 2014; Ferreira et al, 2007; Borges & Milward‐de‐Azevedo, 2017), Minas Gerais (Bernacci et al, 2014; Cervi & Imig, 2013; Imig et al, 2018), Paraíba (Tölke et al, 2011) and the Chapada do Araripe in northeast Brazil (Souza, Silva & Loiola, 2021). Passiflora is the most species‐rich genus (153 species, 85 endemics), and is widely distributed (“Passiflora in Flora do Brasil 2020 em construção,” 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, a new project named ‘Survey and scientific exploitation of the flora of the UHE Belo Monte’ was initiated, in which inventories and taxonomic studies of different plant groups have been performed, such as the description of a new species of Passifloraceae (Koch et al ), and the guides of Abreu et al () and Cardoso et al (), which recorded 92 and 50 species of Orchidaceae and Zingiberales, respectively. As for Bromeliaceae, De Mello et al () and Koch et al () together recorded 20 species, and the genus Aechmea was one of the most diverse.…”
mentioning
confidence: 99%